Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 10732 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Karenia G.Hansen & Moestrup, 2000" ] } The dataset includes 10732 records from 54 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0011321-200127171203522/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences